The effects of pre-treatments, wood-cement ratios and partial cement substitution by gypsum on Prosopis chilensis wood composites - Ali Abdelrhman Mohammed, Hamdon; Md. Tahir, Paridah; Othman, Mohd Shahwahid; Abdul Samad, Abdul Rahim; Ahmed Abdalla, Ashraf Mohamed (Springer Verlag, 2015)
The aim of this work was to study the effects of pre-treatments, wood-cement ratios and partial cement substitution by gypsum on Prosopis chilensis wood composites. Using ASTM D1037-7, the study reveals that the mechanical properties of the composites are improved by the addition of gypsum treatment, and the lower substitution percentages (10, 20 %) are found to improve the compressive strength. Increasing the substitution percentages by more than 20 % causes a reduction in the density of the aggregates, which negatively affects the compressive strength of the cement composites.